Pemajasan J.S Khairen dalam Novel Dompet Ayah Sepatu Ibu Sebagai Unsur Gaya Kepengarangan: Kajian Stilistika - Ahfalah, Mamix (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2024)
This study aims to describe the form of expository style, meaning and function of expository, and authorial style based on expository in the novel Dompet Ayah Sepatu Ibu by J.S. Khairen. This study uses a stylistic analysis method with the stages of data reduction, classification, description, interpretation, and analysis of results. The data in this study were obtained through recording techniques by identifying quotations in the novel Dompet Ayah Sepatu Ibu by JS Khairen that contain expository style. The results of the study indicate that the dominant type of expository style in the novel Dompet Ayah Sepatu Ibu is comparative figures of speech, especially similes and metaphors, with 48 out of 146 quotations using both figures of speech. Similes are used to describe events or characters in a concrete way, while metaphors provide deeper and more symbolic meanings. Expository in this novel plays a role in creating images, clarifying emotional expressions, and enriching characterization of characters. J.S. Khairen's authorial style tends to be expressive and reflective, with the use of explicit and implicit comparisons to strengthen emotional messages and symbolic meanings in the story. The conclusion of this study is that the novel Dompet Ayah Sepatu Ibu by J.S. Khairen uses a lot of comparative figures of speech, especially similes and metaphors, which function to build images, clarify emotions, and enrich characterization of characters. Khairen's writing style tends to be expressive and reflective, with the use of metaphors that strengthen symbolic meanings and deepen emotional conflicts in the story. Abstrak Penelitian ini bertujuan untuk mendeskripsikan bentuk gaya pemajasan, makna dan fungsi pemajasan, serta gaya kepengarangan berdasarkan pemajasan dalam novel Dompet Ayah Sepatu Ibu karya J.S. Khairen. Penelitian ini menggunakan metode analisis stilistika dengan tahapan reduksi data, klasifikasi, deskripsi, interpretasi, dan analisis hasil. Data dalam penelitian ini diperoleh melalui teknik pencatatan dengan mengidentifikasi kutipan dalam novel Dompet Ayah Sepatu Ibu Karya JS Khairen yang mengandung gaya pemajasan. Hasil penelitian menunjukkan bahwa jenis gaya pemajasan yang dominan dalam novel Dompet Ayah Sepatu Ibu adalah majas perbandingan, khususnya simile dan metafora, dengan 48 dari 146 kutipan menggunakan kedua majas tersebut. Simile digunakan untuk menggambarkan peristiwa atau karakter secara konkret, sedangkan metafora memberikan makna yang lebih dalam dan simbolis. Pemajasan dalam novel ini berperan dalam menciptakan imaji, memperjelas ekspresi emosional, serta memperkaya karakterisasi tokoh. Gaya kepengarangan J.S. Khairen cenderung ekspresif dan reflektif, dengan pemanfaatan perbandingan eksplisit maupun implisit untuk memperkuat pesan emosional dan makna simbolis dalam cerita.